SOLAR WATER HEATER WITH SHELL AND HELICAL COILED TUBE HEAT EXCHANGER AS A STORAGE TANK (Journal of Engineering, 2011)
In this work an experimental study is performed to evaluate the thermal performanceof locally made closed loop solar hot water system using a shell and helical coiled tubeheat exchanger as a storage tank. Several measurements are taken include inlet and outlettemperatures of both collectors and supply water and temperature distribution within thestorage tank. This is beside the water flow rate in both collectors and load cycle. Themain parameters of the system are obtained.